2006
DOI: 10.1111/j.1399-5618.2006.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral cortical thinning in bipolar disorder

Abstract: Objective:  This study was conducted to explore differences in cortical thickness between subjects with bipolar disorder and healthy comparison subjects using cortical surface‐based analysis. Methods:  Brain magnetic resonance images were acquired from 25 subjects with bipolar disorder and 21 healthy comparison subjects. Cortical surface‐based analysis was conducted using the Freesurfer application. Group differences in cortical thickness, defined by the distance from gray/white boundary to the pial surface, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
203
5
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 272 publications
(240 citation statements)
references
References 58 publications
(80 reference statements)
30
203
5
2
Order By: Relevance
“…In the left hemisphere, significant decreases in cortical thickness were observed in the middle frontal cortex (2. Lyoo et al (2006) found a significant reduction in the posterior cingulate in patients with bipolar disorder, including both males and females, we found nonsignificant cortical thinning in the male group but significant thickening in the female group.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…In the left hemisphere, significant decreases in cortical thickness were observed in the middle frontal cortex (2. Lyoo et al (2006) found a significant reduction in the posterior cingulate in patients with bipolar disorder, including both males and females, we found nonsignificant cortical thinning in the male group but significant thickening in the female group.…”
Section: Discussioncontrasting
confidence: 40%
“…Other regions showed differences in cortical thickness, but these differences were not significant (p > .05). Lyoo et al (2006) also used a surface-based reconstruction algorithm and found significant cortical thinning in bipolar disorder patients. In the left hemisphere, significant decreases in cortical thickness were observed in the middle frontal cortex (2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mood symptoms were assessed with the Young Mania Rating Scale (YMRS) 20 and the Hamilton Depression Rating Scale (HAM-D), 21-item version. 21 All raters were trained to administer the scales; the results were assessed for inter-rater reliability. After inclusion and initial evaluation, patients were followed up with weekly screenings until remission of manic symptoms, at which point they were reassessed and blood sampling was carried out again.…”
Section: Methodsmentioning
confidence: 99%
“…However, a right hemisphere involvement in BD has been suggested by findings of decreased gray matter volume in right prefrontal and parietal lobes (Lyoo et al, 2004;Adler et al, 2005) as well as cortical thinning in right superior parietal areas (Lyoo et al, 2006). In addition, neuroimaging and neurophysiological studies revealed atypical functional brain organization, particularly involving the right hemisphere rather than the left (e.g., Grisaru et al, 1998;Rubinsztein et al, 2001;Townsend et al, 2010).…”
Section: Introductionmentioning
confidence: 99%